HUKUM SEBAGAI INSTRUMEN KEBIJAKAN PUBLIK DALAM IZIN USAHA PERTAMBANGAN BATUBARA - Radjikan Radjikan (Jurnal Widya Publika, 2020)
Indonesia is known as an international coal supplier, as in Borneo. The March 2007 abare report (Australian bureau research for agriculture and economic resource) has placed Indonesia as the world's largest coal supplier (about 25%) in the world, followed by Australia, South Africa, China, the Russian, Colombian, and United States. Massive uncontrolled coal deployment, one day it's going to cause big trouble. On the negative side, this actually encourages both national and foreign private companies to achieve even greater coal extinctions. Therefore, governments should actually be working on the redefinition and reorientation of the mining exploitation to be truly beneficial to the people. There are two problems that appear: 1) How is the law as a public policy instrument in coal mining business license?, 2) How does the institutional public policy model in mining permissions? To answer the issue is used descriptive research method analysis so that it is concluded that: Mining Problems in Indonesia lies in the exploitation of coal mining that is so great to overlook the interests of local communities and the environment. The role of law as a public policy instrument can be poured through coal mining permissions. This permission policy uses an institutional public policy model where the government is legitimizing licensing. The legitimacy has implications in the sanctions of any violations in the field of coal mining both in the form of criminal sanctions and administrative sanctions. This policy is also universal.